Gambaran Kadar Glukosa Darah Sewaktu Pada Penderita Hipertensi di Puskesmas II Mendoyo - Sarihati, I Gusti Agung Dewi; Pratiwi, Putu Dita; Swastini, I Gusti Agung Ayu Putu (Jurnal Analis Kesehatan, 2021)
Description of Blood Glucose Levels in Hypertension Patients in Mendoyo Public Health Center  Abstract Hypertension is a degenerative disease that still affects many people in Bali Province. Hypertension occurs due to many factors where it can start from genetics and lifestyle. Hypertension can lead to insulin resistance which is the main cause of increased blood glucose, so that people who suffer from hypertension have the risk of suffering from diabetes mellitus. The purpose of this study is to describe the current blood glucose levels in  patients with hypertension at Puskesmas II Mendoyo. Method this research  uses descriptive quantitative method involving 30 respondents through purposive sampling technique. The research was conducted in March - April 2021. Data collection was carried out by filling out questionnaires and examining blood glukose level with POCT EasyTouch GCU. The results showed that (13.3%) patients with hypertension had blood glucose levels in the non-DM category, (80%) with the uncertain DM category, and (6.7%) in the DM category. The average blood glucose level is 120.7 mg/dl with the lowest level is 84 mg/dl and the highest level up to 273 mg/dl. In conclusion, most patients with hypertension have blood glucose levels during the uncertain DM category.Keywords: blood glucose levels; hypertension; diabetes melitus